Research or teaching? That is the problem: A narrative inquiry into a Chinese college English teacher’s cognitive development in the teaching-research nexus - Ni, Hui; Wu, Xinxin (Frontiers in Psychology, 2023)
This narrative inquiry traces a Chinese college English teacher’s cognitive transformation in the teaching-research nexus over a 4-year time period from the perspective of sociocultural theory (SCT). Several stories were narrated based on the data from reflective journals, literature reading notes, and interaction notes to show how the participant walked out of the teaching-research contradiction and finally achieved professional development. The findings indicate that the college English teacher’s perception of the research-teaching nexus developed when she actively exercised her agency to take part in social interactions in a supportive sociocultural environment with the regulation of appropriate mediational tools. The conceptual progress in the research-teaching nexus finally contributed to her professional development in both teaching and research. The findings of this study have implications for non-key universities and their academics on how to effectively promote teaching-research integration.